Dye-free coloration and flame retardancy of surface-modified polyacrylonitrile fibers. Issue 1 (6th December 2019) - Cao, Jiliang; Meng, Chunli; Fan, Ji
Abstract : In this study, polyacrylonitrile (PAN) fibers were modified with triethylenetetramine (TETA) and subsequently treated with sodium hydroxide (NaOH). The influence of TETA and sodium hydroxide concentration, sodium hydroxide treatment temperature and time on the color and structure of the PAN fibers is discussed. It is shown that when treated with sodium hydroxide, the TETA-modified PAN fibers exhibit excellent flame retardancy and good colorfastness properties. Fourier transform infrared spectrometry analysis of the modified PAN fibers shows a gradual decrease in the characteristic –CN absorption peak at 2243 cm −1, while new absorption peaks for –C=N, –C–N and –NH2 functional groups appear at 1650, 1560 and 3600–3300 cm −1, respectively, confirming changes in the chemical structure of the fibers. In addition, the powder X-ray diffraction data show damage to the physical structure of the fibers in the form of decreased crystallinity and crystal completeness, while the scanning electron microscopy data indicate a significant increase in fiber diameter and surface roughness. These results demonstrate that enhanced flame retardancy and dye-free coloration of PAN fibers can be obtained by TETA and sodium hydroxide modification.